International Meeting of the Ballad Researchers in Vilnius - Liugaitė-Černiauskienė, Modesta (Tautosakos darbai, 2019)
Having accepted the suggestion from the International Ballad Commission / Commission internationale pour l’étude de la chanson populaire / Kommission für Volksdichtung, the Institute of Lithuanian Literature and Folklore organized the research conference “Human Relationships in and through Songs: Meanings and Contexts”, which took place in Vilnius on May 20–24, 2019. This scholarly event was the 49th conference of this organization by the folksong tradition researchers from all over the world and the first of its kind in Lithuania. Forty-four researchers representing over 20 countries in Europe, America and Asia made presentations on various historical and modern forms of folksong, followed by inspiring discussions. The collection of the conference abstracts can be obtained in the libraries or online: http://www.llti.lt/failai/Human%20Relationships+%20(1).pdf. Articles based on the conference presentations will be included into the special issue of the journal Tautosakos darbai / Folklore Studies published in the first half of the 2020.